ANALYSIS OF FINANCIAL LITERACY LEVELS IN INDONESIAN MASTER VOCATIONAL SCHOOL STUDENTS - Dewi Sulistyani; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2022)
This study aims to analyze the level of financial literacy among students at the Indonesian Master Vocational High School (SMK). Financial literacy is a crucial skill for students in managing personal finances, making financial decisions, and preparing for a better economic future. The research method used a quantitative approach by distributing questionnaires to students at the Indonesian Master Vocational High School as respondents. The results showed that the students' financial literacy level was in the moderate category, where most students understood the basic concepts of financial management, but still needed improvement in aspects of investment, financial planning, and financial risk management.